A CASE OF PRIMARY HYPERPARATHYROIDISM WITH DEPRESSIVE STATE - SHIMIZU, Fumio; SAITO, Yumiko; HANEDA, Tadashi; NAGASE, Seiichi (Japanese Journal of National Medical Services, 1994)
The case was a 67-year-old male patient who presented with depressive state, and later on with disturbance of consciousness. He was diagnosed as having primary para-thyroidism from 16. 6 ng/ml of elevated value of parathyroid hormone (PTH-C). Therapy of psychiatric symptoms were administration of antipsychiatric drugs, antidepressants and other drugs and parathyroidectomy. There have been few reports published concerning the psychiatric symptoms associated with primary parathyroidism in Japan. We report here in a case of primary parathyroidism with psychiatric symptoms together with a re-view of the literature.